2017
DOI: 10.1186/s12871-017-0362-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of VividTrac®, Airtraq®, King Vision®, Macintosh Laryngoscope and a Custom-Made Videolaryngoscope for difficult and normal airways in mannequins by novices

Abstract: BackgroundDirect laryngoscopy remains the gold standard for endotracheal intubation and is preferred by experienced operators. However, an increasing number of reports currently support videolaryngoscopy, particularly for novice users. The widespread use of videolaryngoscopy may be limited due to financial limitations, especially in low-income countries. Therefore, affordable single-use scopes are now becoming increasingly popular. We sought to compare these new scopes with direct laryngoscopes and the previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 27 publications
1
28
2
Order By: Relevance
“…Generally, in routine tracheal intubation, videolaryngoscopy is easier to learn than direct laryngoscopy for novice or inexperienced operators . Double‐lumen tube intubation is more complex than routine tracheal intubation, but it has not been determined whether videolaryngoscopes have any advantages in double‐lumen intubation specifically for novices.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, in routine tracheal intubation, videolaryngoscopy is easier to learn than direct laryngoscopy for novice or inexperienced operators . Double‐lumen tube intubation is more complex than routine tracheal intubation, but it has not been determined whether videolaryngoscopes have any advantages in double‐lumen intubation specifically for novices.…”
Section: Discussionmentioning
confidence: 99%
“…In a Szalast et al study [16], intubation with Airtraq was significantly shorter than that with Macintosh (26 vs. 53 s, respectively). Rendeki et al [24] indicated that Airtraq was superior to the Macintosh laryngoscope in difficult airway intubation performed by novice users. This finding is in line with studies by other researchers [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Airtraq is one of the relatively inexpensive and widely used video-laryngoscopes in China. 6 , 18 Airtraq adopted in the experiment attributed to less haemodynamic stimulation following tracheal intubation in comparison with Macintosh laryngoscope. 7 , 19 , 20 This finding probably reflects the fact that Airtraq provides a view of glottis without the need to align the oral, pharyngeal and tracheal axes, and therefore requires less force during laryngoscopy.…”
Section: Discussionmentioning
confidence: 99%